Aplikasi Sistem Informasi Geografi (SIG) untuk Pemetaan Akuifer di Kota Denpasar - JUITA, HARIANJA; SUYARTO, R.; NUARSA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.3, No.4, Oktober 2014, 2014)
ABSTRACT Application of Geographic Information System (GIS) for Mapping of Aquifers in Denpasar City Ground water is the water contained in the soil or rock layers below the soil surface. Water resources derived from groundwater generally directly used to meet the needs of clean water daily. Ground water is used each time would decline both in quality and quantity along with the number of people who exist in an area. The aim of this research is to examine characteristics of aquifer and find out direction of the groundwater flow. Descriptive method selected as the method in this research, which is reads and records forms data to find out types aquifer, aquifer thickness and the permeability of aquifer. Determining the point of wells location is using purposive sampling method and to analyze the aquifer characteristics data likes water quality (eg; temperature, acidity, total dissolved solids), direction groundwater flow, aquifer thickness, aquifer types and the permeability of aquifer using Spline method and IDW (Inverse Distance Weighting). The results of this research are map of temperature, total dissolved solids, pH, aquifer types, aquifer thickness, the permeability of aquifer and groundwater flow. There are poor quality of groundwater in Denpasar area (west, east, north and south area) shows by their temperature and acidity. On the other hand, the total dissolved solids shows good water quality in east Denpasar area only. Depth of the unconfined aquifer ranging from 10 - 40 m (deep) up to > 40 m (very deep), thickness of unconfined aquifer is 30 m (deep) up to > 40 m (very deep), permebility unconfined aquifer are slow, very slow and fast. Depth of confined aquifer start from 40-100 m (deep) up to >100 m (very deep), thickness confined aquifer are 40 m (shallow), 60 m (deep) up to >100 m (very deep), permeability of confined aquifer both slow and fast. Unconfined aquifer and confined aquifer generally are sands, gravel, sandstone, volcanic ash and limestone. Groundwater flow from north to south.   Keyword : Aquifer , Geographic Information System (GIS), Ground water
Keywords: Aquifer; Geographic Information System (GIS); Ground water